Growth response of pak choi (Brassica rapa L.) on different concentrations and intervals of eco-enzyme applications - Soverda, Nerty; Swari, Elly; Neliyati, Neliyati; Putri, Desma; Wahyuni, Dilla (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Vegetable cultivation using eco-enzyme application is one way to improve its production. The study aimed to evaluate the growth response of pak choi using eco-enzyme in several concentrations and its interval. The experiment used a randomized complete block design with two factors (concentrations and interval of eco-enzyme applications). The results showed that the application of eco-enzyme with a concentration of 30 mL L-1 indicated an optimal growth stimulator in pak choi, but it was not significantly different as compared to 50 mL L-1. The application of eco-enzyme twice a week was able to stimulate plant growth including plant height, number of leaves, leaf area, shoot fresh weight, and root fresh weight. Furthermore, there was a linear correlation between leaf area and plant height, leaf number, shoot fresh weight, and root fresh weight that ranged from weak to strong levels. It is recommended to apply eco-enzyme at a concentration of 30 mL L-1 twice a week for optimal pak choi production. Keywords: correlation, leafy vegetable, green olericulture, organic fertilizer, plant booster